Neutrophil elastase inhibitor reduces ventilation-induced lung injury via nuclear factor-κB and NF-κB repressing factor in mice. (August 2014) - Li, Li-Fu; Lai, Yi-Ting; Chang, Chih-Hao; Lin, Meng-Chih; Liu, Yung-Yang; Kao, Kuo-Chin; Tsai, Ying-Huang
Mechanical ventilation used in patients with acute lung injury can damage pulmonary epithelial cells through production of inflammatory cytokines, oxygen radicals, and neutrophil infiltration, termed ventilator-induced lung injury. Neutrophil elastase, nuclear factor-κB (NF-κB), and NF-κB repressing factor (NRF) have previously been shown to participate in the regulation of macrophage inflammatory protein-2 (MIP-2) during airway inflammation. However, the mechanisms regulating interactions among mechanical ventilation, neutrophil influx, and NF-κB/NRF remain unclear. Thus, we hypothesized that neutrophil elastase inhibitor attenuated ventilation-induced neutrophil recruitment and MIP-2 production through inhibition of the NF-κB/NRF pathway. Male C57BL/6 mice were exposed to low-tidal-volume (6 mL/kg) or high-tidal-volume (30 mL/kg) mechanical ventilation using room air with or without 2 µg/g NF-κB inhibitor SN50 or 6 µg/g NRF short interfering RNA or 100 µg/g neutrophil elastase inhibitor administration. Nonventilated mice served as a control group. Evan blue dye, lung wet-to-dry weight ratio, free radicals, myeloperoxidase, histopathologic grading of lung tissue, inflammatory cytokines, Western blot of NF-κB and NRF, and gene expression of NRF were measured to establish the extent of lung injury. Neutrophil elastase inhibitor ameliorated high-tidal-volume ventilation-induced lung injury, neutrophil influx, production of MIP-2 and malondialdehyde, activation of NF-κB and NRF, apoptotic epithelial cell death, and disruption of bronchial microstructure in mice. Mechanical stretch-augmented acute lung injury was also attenuated through pharmacological inhibition of NF-κB activity by SN50 and NRF expression by NRF short interfering RNA. Our data suggest that neutrophil elastase inhibitor attenuates high-tidal-volume mechanical ventilation-induced neutrophil influx, oxidative stress, and production of MIP-2, at least partly, through inhibition of NF-κB/NRF pathway. Understanding the protective effects of neutrophil elastase inhibitor associated with the reduction of MIP-2 allow clarification of the pathophysiological mechanisms regulating severe lung inflammation and development of possible therapeutic strategies involved in acute lung injury.